Fatal chickenpox pneumonia in an asthmatic patient on oral steroids and methotrexate. Issue 4 (April 1995) - Gatnash, A A; Connolly, C K
Abstract : A 49 year old man with a long history of severe chronic asthma, treated with oral corticosteroids and weekly doses of methotrexate, contracted chickenpox from his son whose chickenpox rash had developed three weeks before presentation. Five days before admission the patient developed a vesicular skin rash which became extensive, with general malaise, bilateral pneumonia, and acute deterioration of his asthma. He died two weeks after admission despite treatment with acyclovir.